Beneficial Effects of Spices in Food Preservation and Safety - Gottardi, Davide; Bukvicki, Danka; Prasad, Sahdeo; Tyagi, Amit K. (Frontiers in Microbiology, 2016)
Spices have been used since ancient times. Although they have been employed mainly as flavouring and colouring agents, their role in food safety and preservation have also been studied in vitro and in vivo. Spices have exhibited numerous health benefits in preventing and treating a wide variety of diseases such as cancer, aging, metabolic, neurological, cardiovascular and inflammatory diseases. The present review aims to provide a comprehensive summary of the most relevant and recent findings on spices and their active compounds in terms of targets and mode of action; in particular, their potential use in food preservation and enhancement of shelf life as a natural bioingredient.